ANALISA PERENCANAAN KAPASITAS PRODUKSI PADA PT. MUNCUL ABADI DENGAN METODE ROUGH CUT CAPACITY PLANNING - Iksan Iksan (Matrik : Jurnal Manajemen dan Teknik Industri Produksi, 2018)
Production capacity planning this company have obstacle in meeting its production target, then company oftentimes unable to fulfill consumer demands. It can be inflict the company loose. The problems is how planning production capacity based on Rough Cut Capacity Planning (RCCP) Method in order to make consumers demand be able to supplied? “ The researcher attempt to resolving problem in PT Muncul Abadi by aiming calculate product capacity plan based on Rough Cut Capacity Planning Method and determine required product. To be useful as consideration for the company in planning production. Forecast done within the coming one year term. Capacity planning base on Rough Cut Capacity Planning (RCCP) Method. From forecast result toward previous demand quantity period within 12 periods we could be make production index schedule and order Bill of Resources with standard time that is 0,000316 hours/kg. Able to know machine capacity need in 1 workday = 8 hours day, with 3 shifts per day, 1 week = 6 workdays, 1 month = 25 effective workdays then : available time per month = 25 effective workdays x 8 hours day x 3 shift per day = 600 hours/month. Available capacity for Washing machine = 1.394 hours/month. Available capacity for Crushing machine = 1.394 hours/month. Available capacity for Pelletizing machine = 1.859 hours/month.